PELAKSANAAN PERATURAN PENGISIAN ULANG AIR MINUM BERDASARKAN PASAL 9 AYAT (3) KEPUTUSAN MENTERI PERINDUSTRIAN DAN PERDAGANGAN NOMOR: 705/MPP/KEP/11/2003 TENTANG PENGISIAN ULANG AIR MINUM DALAM KEMASAN DI KOTA PEKANBARU - Fauzir, Rifa Yendi; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
ABSTRACTAs juridical, the government had the rule of intelectual property right which guarantee the creation in ilegal practice and crime. According to the Indonesia ratification in the international agreement needed the law of intelectual property to pay attention about the necessity of society, especially about brand. Whereby, a lot of the problems or violation that happens about brand. Especially in the violation on the water filling up .Related to the problem above, the formulations of the problem in this research are : firstly, the rules of filling up on the drinking water based on the article 9 paragraph 3, the decision of Industri and trade ministry number : 705/MPP/Kep/11/2013 about the filling up on the drinking water in Pekanbaru. Secondly, the protection on the use of the brand gallon of the drinking water committed by the agents in Pekanbaru.This is a sociology juridical reserch, because the writer directly conducted this research in the its location to give the completely and clearly picture about the problem. This study was done in Industry and trade agency in Pekanbaru. While, the population and sample in this research is all participants are involved in the research problem.The data sources used are primary data, secondary data, and tertiery data. The data collection techniques in this reseach are observarion, interview, questionnaire, and documentation. From the research findings, there are three main problems, namely : firstly, based on the industry and trade ministry that writer described above that the rules should be applied, yet still a lot of the violations that committed by the agents, even they do not know the rules because there is no socialiszation. Secondly, the protection on the use of the brand gallon of the drinking water committed by the agents still has the weakness because the tolerance still applied for the violator. Finally the writer would like to propose recommendation that the rules must be applied, so that there is no violation and to guarantee the law protection for each agent who is doing ilegal practice and the crime about brand.Keyword : Refueling Water - Water Depot - Kepmenrindag Nomor: 705/MPP/Kep/11/2003